Analysis Of The Quality Of The Da'wah Website Sesaat.Id Pt Bageur Solusi Indonesia Using The Webqual 4.0 Method - Biktra Rudianto; Muhammad Handy Gusyon; Anggi Puspitasari (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
PT Bageur Solusi Indonesia has one of the rather well-known dakwah websites with temporary domain addresses. Id because during the creation of the dakwah website, The id has never measured the quality of the website and received input and advice from the dakwah user websites. The dakwah website must always increase its quality so that the quality of information, interaction, and use always increase to be better. Because in islamic writing, the prayer schedule and Koran reading must be taken very seriously in written and written content on the website. As for the purpose of this study to measure the quality of the website felt by user or user. The study USES a webqual 4.0 method using a SPSS version 25.0 sample used in research and data collection of 92 respondents by sampling methods using abstract samples and dissemination of questionnaire using Google form on the dakwah website for the instant. This study shows that based on a double linear regression test analysis the usability quality results of 0.358 and information quality of 0.309 and for service ediquality of 0.374, which means the website is sterling quality. Then the correlation and determinations test came up with 73.6% and the remaining 26,4% Was affected by another factor not tested in this study. Based on the new data based on value value of 25,390, which means PT.Bageur was able to acquire the value of usability quality 21.365 and information quality service of 17.953. And from the test f of 190.487 the significance of 0,000, the quality of the website has significant value.